Implementation Of Flipped Classroom To Foster Students’ Learning, Motivation And Engagement At Second Grade Of SMA Kartika Kendari - Indah, Sulfajriyani; Sahlan, Sahlan; Alberth, Alberth (Halu Oleo University, 2017)
Teaching reading by using Flipped learning is rarely-researched in field of education especially in Indonesia. This study was conducted to find out the improvement of second year students’ reading comprehension, motivation and engagement after they were taught using Flipped classroom at SMA Kartika Kendari. The study was designed to employ a mixed method. The total number of the participants was 60, which were grouped into two classes, namely an experimental class and a control class. To draw samples, the researcher used random sampling technique. Instrument used to collect data were a reading comprehension test, a questionnaire of motivation, a questionnaire of students’ engagement and an interview script to acquire qualitative data. The reading test consisted of 13 multiple choice items. The questionnaire of motivation consisted of 17 close-ended items and there were 16 statements used in the questionnaire of students’ engagement. Additionally, descriptive statistic and t analysis were performed to obtain quantitative data. Results of post test showed that there was an improvement in the students’ reading comprehension after they were taught using Flipped classroom. Besides, the students’ motivation also increased and so was their engagement after they were taught using Flipped classroom. In addition, qualitative data indicated data that the students enjoyed and had a high willingness to participate in the learning process especially when they were watching videos and doing assignment.